Globalización neoliberal, ciudadanía y democracia. Reflexiones críticas desde la teoría política de Boaventura de Sousa Santos - Agulló Bonet, Antoni Jesús (Nómadas. Critical Journal of Social and Juridical Science, 2008)
The main objective of this paper is to raise the need to revise the hegemonic model of democracy and it’s consecutive concept of citizenship by taking as a frame of reference the critique and emancipatory political theory of Boaventura de Sousa Santos. There is a need of doing this given the predominance of the processes of structural inequality and social exclusion produced by neoliberal globalization. The low-intensity democratic political system is questioned by Santos. With his proposal to reinvent the State and democracy, the Portuguese sociologist tries to found a new democratic culture based on inclusive, community and participatory elements.
Keywords: Inequality; Social exclusion; Citizenship; Neoliberal globalization; Democracy; Political participation